“Best of both worlds”: A students-as-partners near-peer moderation program improves student engagement in a course Facebook group - Jay, Mohammad; Lim, Michelle; Hossain, Khalid; White, Tara; Naqvi, Syed Reza; Chien, Kevin; Haffie, Tom (International Journal for Students as Partners, 2019)
Social media platforms like Facebook are designed to facilitate online communication and networking, primarily around content posted by users. As such, these technologies are being considered as potential enhancements to traditional learning environments. However, various barriers to effective use may arise. Our research investigated the effectiveness of a students-as-partners near-peer moderation project, arising from collaboration between instructors and senior students, as a vehicle for enhancing student interaction in a Facebook group associated with a large introductory science course. The quantity and quality of sample posts and comments from Facebook groups from three successive academic years were evaluated using a rubric that considered characteristics such as civility, content accuracy, critical thinking and psychological support. Two of these groups were moderated by near-peer students while the third group was not moderated. We found improved course discussion associated with moderated groups in addition to benefits to moderators and the faculty partner. This suggests that near-peer moderation programs working in collaboration with faculty may increase student engagement in social media platforms.